Assessment of disease burden in the arsenic exposed population of Chapar village of Samastipur district, Bihar, India, and related mitigation initiative - Kumar, Arun; Rahman, Md. Samiur; Ali, Mohammad; Salaun, Pascal; Gourain, Arthur; Kumar, Suresh; Kumar, Ranjit; Niraj, Pintoo Kumar; Kumar, Mukesh; Kumar, Dhruv; Bishwapriya, Akhouri; Singh, Shreya; et al. (Environmental science and pollution research international, 2022)
Fast growing arsenic menace is causing serious health hazards in Bihar, India, with an estimated 10 million people at risk. The exposed population is often unaware of the problem, which only amplifies the burden of arsenic health effects. In the present study, we have assessed the current situation of arsenic exposure in Chapar village of Samastipur district, Bihar. The health of the inhabitants was assessed and correlated with (1) arsenic concentrations in the groundwater of individual wells and (2) arsenic concentration found in their hair and urine. Altogether, 113 inhabitants were assessed, and 113 hair, urine and groundwater samples were collected. The health study reveals that the exposure to arsenic has caused serious health hazard amongst the exposed population with pronounced skin manifestations, loss of appetite, anaemia, constipation, diarrhoea, general body weakness, raised blood pressure, breathlessness, diabetes, mental disabilities, diabetes, lumps in the body and few cancer incidences. It was found that 52% of the total collected groundwater samples had arsenic levels higher than the WHO limit of 10 µg/l (with a maximum arsenic concentration of 1212 µg/l) and the reduced arsenite was the predominant form in samples tested for speciation ( N = 19). In the case of hair samples, 29% of the samples had arsenic concentrations higher than the permissible limit of 0.2 mg/kg, with a maximum arsenic concentration of 46 µg/l, while in 20% exposed population, there was significant arsenic contamination in urine samples > 50 µg/l. In Chapar village, the probability of carcinogenic-related risk in the exposed population consuming arsenic contaminated water is 100% for children, 99.1% for females and 97.3% for male subjects. The assessment report shared to the government enabled the village population to receive two arsenic filter units. These units are currently operational and catering 250 households providing arsenic-free water through piped water scheme. This study therefore identified a significant solution for this arsenic-exposed population.